The burden of symptomatic skeletal events in castrate-resistant prostate cancer patients with bone metastases at three Canadian uro-oncology centres - Saad, Fred; Fleshner, Neil E.; So, Alan; Le Lorier, Jacques; Perrault, Louise; Poulin-Costello, Melanie; Rogoza, Raina; Robson, Ewan J.D. (Canadian Urological Association Journal, 2018)
Introduction: Metastatic bone disease in castrate-resistant prostate cancer (CRPC) carries risks of significant morbidity, including symptomatic skeletal events. We estimated the healthcare resource costs of managing skeletal events. Methods: A retrospective chart review was conducted for patients who died from or were treated palliatively for metastatic CRPC from 2006–2013 at Centre Hospitalier de l’Université de Montréal (Montreal), Princess Margaret Cancer Centre (Toronto), or Vancouver General Hospital (Vancouver). Results: Of 393 patients, 275 (70%) experienced 833 events (85 per 100 patient-years), with a median time to first event of 17.6 months (95% confidence interval [CI] 15.3, 21.7). The mean metastatic bone disease-related healthcare resource use cost (2014 Canadian dollars) estimate for patients without symptomatic skeletal events was 9550 and between 22 101 (observed) and 34 615 (adjusted) for patients with at least one event. Fewer patients in Montreal (55%) experienced events compared to Toronto (79%) or Vancouver (76%). Median time to first event was longer in Montreal (25.0 months [18.5, 32.6]) than in Toronto (14.6 months [9.7, 16.8]) or Vancouver (17.3 months [14.8, 24.0]). More patients received bone-targeted therapy in Montreal (64%) and Toronto (60%) than in Vancouver (24%). Bone-targeted therapy was mostly administered every 3–4 weeks in Montreal and every 3–4 months in Toronto. Conclusions: Metastatic bone disease-related healthcare resource use costs for Canadian CRPC patients are high. Symptomatic skeletal events occurred frequently, with the incremental cost of one or more events estimated between 12 641 and 25 120. Symptomatic skeletal event incidence and bone-targeted therapy use varied considerably between three Canadian uro-oncology centres. An important limitation is that only patients who died from prostate cancer were included, potentially overestimating costs.